Shake-table testing of unreinforced fly ash brick masonry model with unreinforced elastomeric isolator - Zoheb Nawaz Md; Mohan S. C.; Sri Kalyana Rama Jyosyula (Scientific Reports)
Abstract Seismic isolation techniques are widely used to mitigate earthquake-induced damage in structures; however, their application in low-cost unreinforced masonry (URM) buildings remains limited. This study investigates the effectiveness of Unreinforced Elastomeric Isolators (UEIs) for improving the seismic resilience of URM structures through comprehensive shake-table testing. A half-scale, single-story masonry model was constructed based on similitude laws and tested under both isolated and non-isolated conditions. The UEI was designed and experimentally characterized before implementation. Free and forced vibration tests were conducted to determine the natural frequencies of the model, followed by shake table tests simulating seven earthquake ground motions. Results indicate that the non-isolated model experienced significant acceleration amplification, whereas the isolated model demonstrated reduced roof acceleration and overall seismic force transmission. Despite observable rocking motion in the isolated case, the total roof displacement was lower than in the non-isolated scenario. Comparisons of base shear and overturning moments further confirmed the improved seismic performance of the UEI-supported model. These findings highlight UEIs as a promising, cost-effective solution for seismic protection of masonry structures, paving the way for further optimization and real-world implementation.